Pengenaan Pajak Pada Perjanjian Pengikatan Jual Beli Hak Atas Tanah - Nadia Githa Wijaya; I PT. GD. Seputra; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2021)
Buying and selling is an deal between the parties about paying a certain price of an item, with the aim of transferring ownership rights. in achieving legal certainty in the sale and purchase of land rights, the parties are bound by an agreement based on an agreement made before a notary. Considering Government Ordinance Number 24 of 1997 concerning Land Registration, the transfer of rights to land only arises after the issuance of a sale and purchase deed by the Land Deed Official, then vague norm arises related imposition of tax in the binding agreement on the sale and purchase of land rights. The formulation of the problem: 1. What is the process of binding agreement on the sale and purchase of land rights related to imposition of tax? 2. What is the form of tax imposition in the agreement to buy and sell rights to land? The research method used was Normative/Literature. Binding agreement on the sale and purchase of land rights is a pre-agreement made because it relates to the imposition of tax in the case of a transfer of rights to land that must be paid in advance to order carry out transactions in the Land Deed Official. The tax imposed in the binding agreement on the sale and purchase of land rights is the income tax for the seller and the Cost of Acquiring Land and/or Building Rights for the buyer.